$9 an hour
that 20% of a penny a second, okayyy!
Answer:
<u>2y - 5 (read below)</u>
Step-by-step explanation:
-8y + 10y = 2y
2 + (-7) = -5
Your expression could/would be:
2y - 5.
Hope this helps!
The nephew would need to use division to isolate x giving him $66.50 to spend
Answer: 2 - 2*sin³(θ) - √1 -sin²(θ)
Step-by-step explanation: In the expression
cos(theta)*sin2(theta) − cos(theta)
sin (2θ) = 2 sin(θ)*cos(θ) ⇒ cos(θ)*2sin(θ)cos(θ) - cos(θ)
2cos²(θ)sin(θ) - cos(θ) if we use cos²(θ) = 1-sin²(θ)
2 [ (1 - sin²(θ))*sin(θ)] - cos(θ)
2 - 2sin²(θ)sin(θ) - cos(θ) ⇒ 2-2sin³(θ)-cos(θ) ; cos(θ) = √1 -sin²(θ)
2 - 2*sin³(θ) - √1 -sin²(θ)